Oxidation Products of 5-Methylcytosine are Decreased in Senescent Cells and Tissues of Progeroid Mice. (3rd February 2018) - Zarakowska, Ewelina; Czerwinska, Jolanta; Tupalska, Agnieszka; Yousefzadeh, Matt J; Gregg, Siobhán Q; Croix, Claudette M St; Niedernhofer, Laura J; Foksinski, Marek; Gackowski, Daniel; Szpila, Anna; Starczak, Marta; Tudek, Barbara; et al.
Abstract: 5-Hydroxymethylcytosine and 5-formylcytosine are stable DNA base modifications generated from 5-methylcytosine by the ten-eleven translocation protein family that function as epigenetic markers. 5-Hydroxymethyluracil may also be generated from thymine by ten-eleven translocation enzymes. Here, we asked if these epigenetic changes accumulate in senescent cells, since they are thought to be inversely correlated with proliferation. Testing this in ERCC1-XPF-deficient cells and mice also enabled discovery if these DNA base changes are repaired by nucleotide excision repair. Epigenetic marks were measured in proliferating, quiescent and senescent wild-type (WT) and Ercc1 −/− primary mouse embryonic fibroblasts. The pattern of epigenetic marks depended more on the proliferation status of the cells than their DNA repair capacity. The cytosine modifications were all decreased in senescent cells compared to quiescent or proliferating cells, whereas 5-(hydroxymethyl)-2′-deoxyuridine was increased. In vivo, both 5-(hydroxymethyl)-2′-deoxyuridine and 5-(hydroxymethyl)-2′-deoxycytidine were significantly increased in liver tissues of aged WT mice compared to young adult WT mice. Livers of Ercc1 -deficient mice with premature senescence and aging had reduced level of 5-(hydroxymethyl)-2′-deoxycytidine and 5-formyl-2′-deoxycytidine compared to aged-matched WT controls. Taken together, we demonstrate for the first time, that 5-(hydroxymethyl)-2′-deoxycytidine is significantly reduced in senescent cells and tissue, potentially yielding a novel marker of senescence.